Hubungan Lama Waktu Pengunaan Gawai dengan Kesehatan Mental Emosional Anak Sekolah - Drama, Banita Ihfatun; Aisyah, Iis; Hudaya, Ahmad Purnama (Jurnal Keperawatan Florence Nightingale, 2024)
The use of gadgets cannot be avoided anymore, from children to adults, because they offer various conveniences. However, this convenience has resulted in an unavoidable increase in gadget use by children, which can have negative effects on their emotional mental health. This research aims to analyze the relationship between the duration of gadget use and emotional mental health in elementary school children. This quantitative study with a correlational design used the Strength and Difficulties Questionnaire (SDQ) and a questionnaire measuring gadget use duration filled out by parents of 5th and 6th grade elementary school children aged 11-12, involving a population of 74 in SDN Licin Cimalaka using total sampling technique. The chi-square test result showed a p-value of 0.684 > 0.05. The study showed that respondents with normal mental health status had a long gadget play duration of 42 respondents (59.1%). The conclusion drawn was that there is no significant relationship between the duration of gadget use and emotional mental health.